Sayings and anecdotes with other popular moralists - Diogenes the Cynic pproximately 323 B.C.; Hard, Robin (Oxford Oxford University Press, 2012)
"Diogenes the Cynic is famed for walking the streets with a lamp in daylight, looking for an honest man. His biting wit and eccentric behavior were legendary, and it was by means of his renowned aphorisms that his moral teachings were transmitted. He scorned the conventions of civilized life, and his ascetic lifestyle and caustic opinions informed the Cynic philosophy and later influenced Stoicism. This unique edition also covers his immediate successors, such as Crates, his wife Hipparchia, and the witty moral preacher Bion. The contrasting teachings of the Cyrenaic school, founded by Aristippos, a pleasure-loving friend of Socrates, complete the volume, together with a selection of apocryphal letters."--Publisher's website.
pt. 1. Diogenes and the early cynics. A humorous portrait of Diogenes and Aristippos -- Diogenes' conversion to the Ascetic life -- The sage as beggar -- Self-characterization -- A short-cut to philosophy -- The world of illusion -- Religion and superstition -- Politicians and rulers -- The sale and enslavement of Diogenes -- Moralistic and traditional -- Diogenes as wit -- Old age and death -- Immediate followers of Diogenes -- Sayings and anecdotes of Crates -- The followers of Crates -- Postscript: Bion of Borysthenes -- Antisthenes as forerunner of cynicism -- pt. 2. Aristippos and the Cyrenaics. Aristippos of Cyrene -- The Cyrenaic School under the younger Aristippos -- The other Cyrenaics -- pt. 3. Apocryphal Letters. Selections from the Cynic letters -- Correspondence of Aristippos.
Includes bibliographic references (pages [xxxv]-xxxviii) and indexes.
Keywords: Diogenes -- pproximately 323 B.C. -- Quotations, maxims, etc; Ethicists -- Quotations, maxims, etc; Philosophers -- Quotations, maxims, etc; Cynicism -- Quotations, maxims, etc; Cynics (Greek philosophy) -- Quotations